Pengetahuan Dan Kepatuhan Minum Obat Hipertensi : Pasien Di RSUD Brigjend H.Hasan Basry Kandangan - Fitriah, Rahmayanti; Faisal, Muhammad; Akbar, Depy Oktapian (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
Hypertension is the third cause of death after stroke and tuberculosis, accounting for 6.7% of all deaths of all ages in Indonesia. Knowledge is the level of patient behavior during treatment and behavior recommended by doctors. Hypertension sufferers must be aware of the importance of high blood pressure, the causes of high blood pressure, the symptoms that are often associated with it, the importance of taking medication regularly and continuously in the long term and the dangers of not taking medication. Patient adherence to treatment is very important because hypertension cannot be cured but must be controlled to avoid fatal complications. The aim of the researchers was to determine the relationship between knowledge level and medication adherence (hypertension patients at Brigjend H. Hasan Basry Kandangan Hospital). The method used is analytic observational with a cross sectional research design using a purposive sampling technique of 300 respondents with a questionnaire measuring instrument. The results of this study indicate that the level of knowledge of hypertension patients at Brigjend H. Hasan Basry Kandangan Hospital from 300 respondents included in the Good category as many as 279 respondents (93%), Enough 21 respondents (7%), and Less 0 respondents (0%). Compliance with taking medication in the high category was 69 respondents (23%), moderate 136 respondents (45.3%), and low 95 respondents (31.7%). The conclusion obtained using the Chi Square test states that there is a significant relationship between the level of knowledge and adherence to taking medication for hypertension patients at Brigjend H. Hasan Basry Kandangan Hospital.